Pelatihan Desain Merek dan Pemasaran Digital Bagi Pelaku UMKM di Desa Mekar Sari - Hilmiatus Sahla; Aris Siregar; Irvan; Alweni Khoiriyah Lubis; Rayhan Nouvalya (Masyarakat Ekonomi Syariah Bogor, 2024)
The existence of MSMEs plays a very important role in supporting the economy of village communities. The mindset of Micro, Small and Medium Enterprises (MSMEs) in Mekar Sari Village, Buntu Pane District, Asahan Regency assumes that without the need for various marketing strategies, their products will still be in demand on the market. This is one of the factors that causes their products to be packaged in a simple and straightforward way. In fact, the packaging design of the product being marketed is the first thing consumers see and can influence their psychology in deciding to buy. The aim of the service is to assist the Mekar Sari Village MSME community in its efforts to increase its productivity by utilizing advances in information technology through print media, banners and branding on products in promotion and marketing.